Zbawcza misja Ducha Świętego według programu duszpasterskiego dla Kościoła w Polsce na lata 2017-2019 - Kowalczyk, Marian (Collectanea Theologica, 2020)
Referring to the pastoral program for the Church in Poland in 2017- 2019, an analysis of the publication of the pastoral committee of the Polish Bishops’ Conference for pneumatology was carried out. It was demonstrated that the pastoral program primarily focused on the presence of the Holy Spirit in the life and mission of Jesus Christ in order to show the saving influence of the Spirit on the human being. Also, the accurate presentation of the salvific activity of the Holy Spirit in the community of God’s people should be appreciated, especially in the sacraments (with special regard to baptism and confirmation) and in charisms. However, the publication in question results in some overemphasis on the flattering approach to the gifts of the Holy Spirit and the depiction of the discernment of spirits. Moreover, the discussion of temptations and criteria for their discernment, although interesting, is not fully developed in view of the difficulties resulting from the inability to precisely distinguish, in charisms, between what man produces and what is the work of the Spirit that surpasses all cognitive abilities. Therefore, apart from pointing out external and internal threats, the program lacks bold references to increasing, far-reaching threats that not only weaken faith, but are also dangerous to the very existence of man, and thus may even lead to his diabolical destruction. Finally, there are few references in the program to such important aspects of pneumatology such as: the role of the Spirit in Mary’s maternal mission, the pursuit of Christian unity, interreligious and intercultural dialogue, and the realization of the kingdom of God until its final fulfilment in the Parousia.